FEATURES OF LOGICAL AND MATHEMATICAL DEVELOPMENT OF PRESCHOOLERS WITH THE HELP OF FLASH GAMES - Polevikova, Olga; Shvets, Tetiana (Educological discourse, 2021)
The article analyzes the problem of logical and mathematical development of senior preschoolers by means of flash games. The importance of mathematical education has been substantiated in accordance with the new educational realities: the needs of the implementation of the Concept for the development of natural and mathematical education (STEM education) and the new Concept for the development of preschool education. Since now mathematics, together with computer science, is becoming an interdisciplinary toolkit, and modern children feel free in the world of information technology, the authors of the article note that it is advisable to use network resources to benefit the educational process and ensure its quality. One of the options for such a network resource are flash games - game interactive platforms that optimize the game process in order to solve educational problems. The authors analyzed the views on the appropriateness of the use of flash games by preschoolers from such foreign scientists as Feliks Gorski, Alex Soares, Adelheid Reinhardt, David Nascimento, Gabriella Domeny, Mozilla Firefox, Peer Dorow, Benjamin Cooper, Zsuzsanna Csarnai Straub. The specificity of the experimental work, which involves two directions, is characterized. In the first educational - stage I is highlighted - propedeutic (criteria: abstraction with indicators - the ability to highlight the most significant characteristics of the object and exclude insignificant signs, where the flash game "Choose transport" was used; analysis with indicators - the ability to determine the relationship of an object and objects; to compare and analyze the data obtained; flash game: "Whose traces?"; synthesis with indicators - the ability to observe the laws of logic, build hypotheses and find out the consequences of reasoning; flash game "When does this happen?"); Stage II - implementation (criteria: classification with indicators - the ability to perform logical operations, deliberately argue them, formulate the grounds for classifying objects; flash games "The artist was mistaken", "Find a pair"; serialization with indicators - the ability to lay out a set of elements in accordance with the connections established between them; flash games: "Find a pair", "Logical connections", "In search of a shadow", "Into the forest for mushrooms", "Let’s play snowballs", "Whose voice is heard on the farm?"); II direction - consulting: work with the teaching staff and with the parents of the pupils. The effectiveness of the work carried out was revealed using five diagnostic methods, carefully described in the article.